(untitled) (Progressive Agriculture, 2022)
A field experiment was conducted to reduce the chemical fertilizers with the integrated use of vermicompost and chemical fertilizers in T. aman rice cultivation. The research was conducted at the Soil Science Division, Bangladesh Institute of Nuclear Agriculture (BINA), Mymensingh during the T. aman season of 2019-20 at BINA farm Mymensingh. Six treatments were used in the experiment. These were T1: Native soil fertility, T2: 100% N from Chemical Fertilizer (CF), T3:70%N from CF, T4: 30% N from vermicompost-3 + 70% N from CF and T5:30% N from vermicompost-4 + 70% N from CF and T6: 100% PKS only. The experiments were conducted in a Randomized Complete Block Design with three replications. The test crop was T. aman rice (Binadhan-17). The treatment T5 gave maximum grain yield (5.5 t ha-1) of T. aman rice followed by 5.4 t ha-1 that did by the treatment T4. But the treatments T5, T4 and T2 gave identical grain yields of T. aman rice. Similar results were observed in case of straw yields of T. aman rice. The maximum total N, P, K and S uptake were also noted with the treatment T5 (30% N from vermicompost-4 + 70% N from CF) followed by the treatment T4 (30% N from vermicompost-3 + 70% N from CF) which were comparable with the treatment T2 (100% chemical fertilizer). The result indicated that 30% N from either vermicompost-3 or vermicompost-4 with 70% N from CF gave comparable yields to the sole application of 100% N from CF alone. Therefore, overall 30% chemical fertilizers (N, P, K and S) could be saved with the integrated use of vermicompost-3 or vermicompost-4 following IPNS in the cultivation of T. aman rice. Progressive Agriculture 32 (2): 96-106, 2021